Establishment of multi-slice computed tomography (MSCT) reference level in Johor, Malaysia - Karim, M. K. A. (Institute of Physics Publishing, 2016)
Radiation doses from computed tomography (CT) are the highest and most hazardous compared to other imaging modalities. This study aimed to evaluate radiation dose in Johor, Malaysia to patients during computed tomography examinations of the brain, chest and abdomen and to establish the local diagnostic reference levels (DRLs) as are present with the current, state- of-art, multi-slice CT scanners. Survey forms were sent to five centres performing CT to obtain data regarding acquisition parameters as well as the dose information from CT consoles. CT- EXPO (Version 2.3.1, Germany) was used to validate the dose information. The proposed DRLs were indicated by rounding the third quartiles of whole dose distributions where mean values of CTDIw(mGy), CTDIvol(mGy) and DLP (mGy.cm) were comparable with other reference levels; 63, 63, and 1015 respectively for CT Brain; 15, 14, and 450 respectively for CT thorax and 16, 17, and 590 respectively for CT abdomen. The study revealed that the CT practice and dose output were revolutionised, and must keep up with the pace of introductory technology. We suggest that CTDI volshould be included in current national DRLs, as modern CTs are configured with a higher number of detectors and are independent of pitch factors.